Surface Modification of Polycaprolactone Scaffold With Improved Biocompatibility and Controlled Growth Factor Release for Enhanced Stem Cell Differentiation - Qin, Xiaoyan; Wu, Yixin; Liu, Shuang; Yang, Lei; Yuan, Hongxia; Cai, Susu; Flesch, Julia; Li, Zehao; Tang, Yujing; Li, Xiaomin; Zhuang, Yi; You, Changjiang; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Polycaprolactone (PCL) has been widely used as a scaffold material for tissue engineering. Reliable applications of the PCL scaffolds require overcoming their native hydrophobicity and obtaining the sustained release of signaling factors to modulate cell growth and differentiation. Here, we report a surface modification strategy for electrospun PCL nanofibers using an azide-terminated amphiphilic graft polymer. With multiple alkylation and pegylation on the side chains of poly-L-lysine, stable coating of the graft polymer on the PCL nanofibers was achieved in one step. Using the azide-alkyne “click chemistry”, we functionalized the azide-pegylated PCL nanofibers with dibenzocyclooctyne-modified nanocapsules containing growth factor, which rendered the nanofiber scaffold with satisfied cell adhesion and growth property. Moreover, by specific immobilization of pH-responsive nanocapsules containing bone morphogenetic protein 2 (BMP-2), controlled release of active BMP-2 from the PCL nanofibers was achieved within 21 days. When bone mesenchyme stem cells were cultured on this nanofiber scaffold, enhanced ossification was observed in correlation with the time-dependent release of BMP-2. The established surface modification can be extended as a generic approach to hydrophobic nanomaterials for longtime sustainable release of multiplex signaling proteins for tissue engineering.